Sleep and circadian rhythm disruption in social jetlag and mental illness. - Foster, R; Peirson, S; Wulff, K; Winnebeck, E; Vetter, C; Roenneberg, T (2013)
Sleep and wake represent two profoundly different states of physiology that arise within the brain from a complex interaction between multiple neural circuits and neurotransmitter systems. These neural networks are, in turn, adjusted by three key drivers that collectively determine the duration, quality, and efficiency of sleep. Two of these drivers are endogenous, namely, the circadian system and a homeostatic hourglass oscillator, while the third is exogenous-our societal structure (social time). In this chapter, we outline the neuroscience of sleep and highlight the links between sleep, mood, cognition, and mental health. We emphasize that the complexity of sleep/wake generation and regulation makes this behavioral cycle very vulnerable to disruption and then explore this concept by examining sleep and circadian rhythm disruption (SCRD) when the exogenous and endogenous drivers of sleep are in conflict. SCRD can be particularly severe when social timing forces an abnormal pattern of sleep and wake upon our endogenous sleep biology. SCRD is also very common in mental illness, and although well known, this association is poorly understood or treated. Recent studies suggest that the generation of sleep and mental health shares overlapping neural mechanisms such that defects in these endogenous pathways result in pathologies to both behaviors. The evidence for this association is examined in some detail. We conclude this review by suggesting that the emerging understanding of the neurobiology of sleep/wake behavior, and of the health consequences of sleep disruption, will provide new ways to decrease the conflict between biological and societal timing in both the healthy and individuals with mental illness.